Annual Plan 1999-2000 State Planning Commission Tamil Nadu - Planning Commission (Planning Commission, 1999)
Annual plan for 1999-2000, the third year of the IX Plan, assumes significance as we have to consolidate the gains of the first two years of the Ninth Plan, and make good the areas of shortfall and maintain the tempo of development in order to achieve the Ninth Plan objectives. In accordance with the approach outlined in the national IX Plan and on the Action Plans on priority areas communicated by the Government of India in July 1998, the State Planning Commission has formulated the Annual Plan for 1999-2000.The State’s IX Plan envisages an outlay of Rs.25. 000 crores and aims at a SDP growth rate of 7% per annum. During the first year of the plan, i.e. 1997-98, the expenditure was Rs.4, 010 crores against an approved outlay of Rs.4.004 crores. For 1998-99, the plan outlay is Rs.4, 500 crores. The approved outlay for the first two years constitute 34 % of the IX Plan outlay. The following, paragraphs give a brief review of the progress in the crucial sectors of the economy in 1998-99.
Annual Plan 1999-2000
Government of Tamil Nadu